Pembelajaran Bahasa Arab Untuk Tujuan Khusus (Arabic For Specific Purposes): Tinjauan Sistematis Dalam Konteks Pendidikan - Salsabila, Anggia Difha; Fikroh, Aulia Nasyithotul; Bazighoh, Zulva Zahro (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Arabic language learning in various educational institutions is still dominated by a general approach, making it less responsive to the specific needs of students who require Arabic for specific professional contexts. This study aims to analyze the characteristics of Arabic for Specific Purposes (ASP) learning, the challenges of its implementation, and its development practices in the context of education, comparing practices in Indonesia and Malaysia. This study uses a qualitative approach with literature study and document analysis methods on scientific articles, curricula, and research reports related to ASP, particularly in Indonesia and Malaysia. The analysis was conducted through theme grouping, synthesis of findings, and comparison of application contexts. The results of the study show that Arabic for Specific Purposes learning requires an adaptive curriculum based on needs analysis, the use of communicative and contextual approaches, and collaboration between educational institutions and the world of work. Differences in practice were found between Indonesia, which tends to be theoretical, and Malaysia, which is more applicative. These findings emphasize the importance of developing a responsive and applicative ASP curriculum to increase the relevance of Arabic learning to the needs of the world of work.